2018
DOI: 10.1111/den.13221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative biliary drainage on postoperative outcome after pancreaticoduodenectomy: An analysis of 1500 consecutive cases

Abstract: Preoperative biliary drain does not increase major complications and mortality rates after pancreatoduodenectomy, but it is associated with higher surgical site infection rates. In jaundiced patients, a bilirubin value greater than 7.5 mg/dL (128 μmol/L) should indicate biliary drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 37 publications
5
43
0
3
Order By: Relevance
“…Surgical outcome is determined by several factors. As already reported, patients with bilirubin levels greater than 7.5 mg/dL showed higher postoperative AEs and morbidity . In our study, there was no difference in postoperative complications based on bilirubin level of 7.5 mg/dL (36% vs 24.1%, P = 0.39), but overall perioperative complication including stent and surgery‐related complication was significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical outcome is determined by several factors. As already reported, patients with bilirubin levels greater than 7.5 mg/dL showed higher postoperative AEs and morbidity . In our study, there was no difference in postoperative complications based on bilirubin level of 7.5 mg/dL (36% vs 24.1%, P = 0.39), but overall perioperative complication including stent and surgery‐related complication was significantly different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative biliary drainage by means of ERCP did not influence perioperative outcomes in the current study. However, this is a controversial topic, since this approach may lead to more infectious complications after PD (28) , although as it has been pointed by Ngu et al (29) , the avoidance of preoperative biliary drainage will prove logistically difficult for most hepato-pancreato-biliary units. A metaanalysis conducted by Wang et al (30) concluded that the current evidence neither supports nor refutes pre-operative biliary drainage for patients with obstructive jaundice needing surgery; however, this review also highlighted the heterogeneity and poor quality of most analyzed studies.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by De Pastena et al 1 This retrospective study identified that preoperative biliary drain does not increase major complications and mortality rates after pancreaticoduodenectomy, but it is associated with higher surgical site infection rates. Herein, we would like to raise the following points.…”
Section: Impact Of Preoperative Biliary Drainage On Postoperative Outmentioning
confidence: 98%
“…To the Editor, We appreciated the Letter by Li et al regarding our manuscript on the impact of preoperative biliary drainage (PBD) on postoperative outcomes after pancreaticoduodenectomy (PD). 1 The manuscript reflects the institutional policy of the jaundice treatment of the patients undergoing PD. Our center is a high volume center, treating patients who had often received a PBD in a country hospital.…”
Section: Reply To: Impact Of Preoperative Biliary Drainage On Postopementioning
confidence: 99%
See 1 more Smart Citation